Microbial synthesis of copper oxide nanoparticles from endophytic Actinomycetes and its postharvest application on Solanum lycopersicum - Chaugule, Vinay V (Journal of Postharvest Technology, 2022)
Selected 2 endophytic actinomycetes were used for the creation of nanoparticles, these types were fit in with Streptomyces. These species  were acknowledged with 16SrRNA gene sequence. Two types were definite as Streptomyces noursei (A-1) and Streptomyces fradiae (A-2).  The biomass haul out of these species were used for the creation of Cu oxide nanoparticles with the CuSO45H2O. The organized  nanoparticles were weathered for depiction with UV visible spectroscopy, FTIR Spectroscopy, X ray Diffraction and Transmission electron  microscopy (TEM) The bio combination of Cu oxide nanoparticles give you an idea about surface plamon resonance (SPR) combination band  in the range 410 to 450 nm. These the bio combination of Cu oxide nanoparticles were spherical formed and crystalline in nature. The  volume of bio combination of Cu oxide nanoparticles lies in between 50 to 100 nm. XRD analysis exposed that both A-1 and A-2  biosynthesized actinomycetal CuO nanaoparticles were crystalline nature.FTIR spectra accredited that presence no. of poles apart bonds and  were most important C-O and N-H bonds.The biologically synthesized CuO nanoparticles are tested for increasing the shelf life of Solanum  lycopersicum. It is also helpfull more than chemical preservatives those they are in routine by the analysis of such biological synthesized  nanoparticles for increasing shelf life of Solanum lycopersicum, it could be applied for other number of food products after or while post  harvesting system.AS far concern with chemical preservatives, it was found that this biologically synthesized CuO nanoparticles are effective  in food preservation.
Keywords: Triticumvulgare; Actinomycetes; Streptomyces; CuSO45H2O and Solanum lycopersicum